Anomalias dentárias e craniofaciais na anemia de Fanconi: revisão sistemática de 158 casos e 46 relatos adicionais - Paula Alves da Silva Rocha (2024)
The present study aimed to conduct a systematic review of the literature on dental and craniofacial anomalies in individuals with Fanconi Anemia, as well as to evaluate the occurrence of these alterations in a cross-sectional study approved by the Research Ethics Committee. The research was conducted in partnership with two Brazilian reference centers, the Hospital das Clínicas of the Federal University of Minas Gerais and the Hospital de Clínicas of the Federal University of Paraná. Fanconi Anemia (FA) is a rare genetic disease and lacks studies on dental and craniofacial characteristics. For the systematic literature review, electronic searches were conducted in six databases, complemented by manual analysis and gray literature. Cross-sectional studies and case reports were included. A total of 19 articles describing 158 cases of FA were analyzed. The estimated prevalence of dental anomalies ranged from 13.3% to 71.4%. Among the 158 individuals, 130 exhibited dental and/or root abnormalities, while 56 presented malocclusion and/or craniofacial anomalies. Our cross-sectional study was based on clinical-radiographic evaluation and included 46 patients diagnosed with FA through chromosomal breakage tests and/or genetic tests. Our study revealed that 93.5% of the patients presented dental and/or craniofacial anomalies, particularly root abnormalities. that 93.5% of patients presented dental/craniofacial anomalies, particularly radicular abnormalities. Males predominantly exhibited eruption/exfoliation anomalies. A higher occurrence of anomalies related to tooth size was observed in individuals who underwent hematopoietic stem cell transplantation at ≥14 years of age. The limited literature and variability of dental and craniofacial anomalies in FA highlight the need to expand and standardize diagnostic criteria for effective monitoring and mitigation of their impact on health and quality of life.